THE EFFECT OF ROLE PLAYING TECHNIQUE APPLIED ON STUDENTS` SPEAKING COMPETENCE - Budi, Kartika Marta (Educate, 2012)
Abstract This study aims to see the effect of the role playing technique application in on students` speaking competence, that covers (1) How is the effect of Role Playing teaching technique applied to the students` speaking competence on experimental class; and (2) How is the effect of conventional teaching applied to students` speaking competence on control class. The subjects are the students of Junior High 2 level book program in YPIA English Course, Jalan Sumatera Branch, Surabaya. The data of this study were the students` scores, and from the tests` scores it can be seen that there is a positive significant difference in the experimental group. The t-test shows that there is an improvement on the students` speaking competence achievement. In conclusion, the role playing application effects on the significant difference on the students speaking competence achievement. Keywords: Role Playing, Speaking Competence